Prevalence of soil-transmitted helminths in remote villages in East Kwaio, Solomon Islands - Humpress Harrington; Richard Bradbury; James Taeka; James Asugeni; Vunivesi Asugeni; Tony Igeni; John Gwala; Lawrence Newton; Chillion Evan Fa`anuabae; Fawcett Laurence Kilivisi; Dorothy Esau; Angelica Flores; et al. (World Health Organization Regional Office for the Western Pacific, 2015)
Objective: Although soil-transmitted helminths (STH) are endemic in Solomon Islands, there are few recent reports on their prevalence. This study aimed to determine the prevalence of STH in residents of remote communities in Solomon Islands. Methods: A cross-sectional convenience-sampled survey of residents of four adjacent villages in Malaita, Solomon Islands was performed in Atoifi and Na'au in April 2011 and in Abitona and Sifilo in April 2012. All residents older than one year were invited to participate, which involved providing a single sample of faeces examined using a modified Kato-Katz technique and completing a questionnaire that asked demographic and STH-related behaviour questions. Results: The overall participation rate was 52.8%, with 402 participants comprising 49.8% males. Hookworm was the predominant STH with only a single case of trichuriasis found in Atoifi. The total prevalence of hookworm was 22.6% (95% confidence interval: 18.6-27.1); the prevalence of hookworm in Abitona, Na'au and Sifilo was 20.0%, 29.9% and 27.4%, respectively, whereas in Atoifi it was 2.3% (P < 0.001). Intensity was low in all villages. Although health behaviours differed significantly between Atoifi and the other three villages, the type of toilet used was the only significant association with hookworm. Discussion: Residents of Atoifi have a relative freedom from STH compared to the other three villages. Rather than a region-wide morbidity control approach, a "one village at a time" approach aiming to eliminate STH and dealing with each village as a separate autonomous unit empowered to manage its own challenges may be a preferred option.